2021
DOI: 10.1158/1940-6207.capr-20-0622
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Message Framing on Cervical Cancer Screening Knowledge and Intentions Related to Primary HPV Testing

Abstract: Numerous national guidelines now include primary human papillomavirus (HPV) testing as a recommended screening option for cervical cancer in the United States yet little is known regarding screening intentions for this specific screening strategy or interventions that may increase uptake. Gain-and loss-framed messaging can positively impact health behaviors; however, there is mixed evidence on which is more effective for cervical cancer screening, with no published evidence examining HPV testing. To help addre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…There is mounting evidence that message framing does not impact intention in the context of cancer screening. A recent study found framed messages increased intention to attend HPV testing compared to a control group, but there was no difference in the effect of gain or loss framed messages (Ogden et al, 2021).…”
Section: Discussionmentioning
confidence: 91%
“…There is mounting evidence that message framing does not impact intention in the context of cancer screening. A recent study found framed messages increased intention to attend HPV testing compared to a control group, but there was no difference in the effect of gain or loss framed messages (Ogden et al, 2021).…”
Section: Discussionmentioning
confidence: 91%